Analysis of biodiesel yield percentage from used cooking oil with variations in stirring time - Dewi, Sukhma Kusuma; Faizal, Ahmad; Sutriyatna, Sutriyatna (Universitas Negeri Semarang, 2025)
The increasing volume of hazardous and toxic waste (B3), particularly from used cooking oil, poses significant environmental and health challenges. One promising solution is converting this waste into biodiesel, thereby promoting renewable energy development while reducing ecological risks. This study investigates the yield percentage of biodiesel produced from waste cooking oil using a magnetic stirrer. The research aims to determine the optimal stirring duration to maximize yield and evaluate the flame duration of the resulting biodiesel. The process involved tool and material preparation, biodiesel production via transesterification, and subsequent data collection and analysis. The findings revealed that the highest biodiesel yield, 58.4%, was achieved at a stirring duration of 45 minutes, whereas the lowest yield, 51.2%, occurred at 60 minutes.